Oxide ion polarizabilities and gamma radiation shielding features of TeO2–B2O3–SiO2 glasses containing Bi2O3 using Phy-X/PSD software. (June 2022) - Geidam, I.G.; Matori, K.A.; Halimah, M.K.; Chan, K.T.; Muhammad, F.D.; Ishak, M.; Umar, S.A.
Abstract: A system of lead-free silica borotellurite glasses containing bismuth oxide was fabricated in accordance with conventional melt-quenching procedure. XRD analysis, UV-Vis spectroscopy and Archimedes principle were employed to unveil the structural, and optical properties. User friendly Phy-X/PSD software was used to ascertain the theoretically radiation shielding features of the glasses. The existence of a diffuse hump in the XRD profile revealed the glasses amorphous characteristic. The molar volume and density values showed nonlinear variation with respect to the increase in mol% of Bi2 O3 . Optical bandgap, index of refraction, oxide ion polarizability (based on index of refraction and bandgap), optical dielectric constant, and third order susceptibility were computed. Various shielding related parameters, specifically, mass attenuation coefficient (MAC), linear attenuation coefficient (LAC), effective atomic number ( Z eff ), effective electron density ( N eff ), mean free path (MFP), half value layer (HVL) and tenth value layer (TVL) were evaluated in the gamma photon energy range between 0.015 MeV and 15 MeV. The results revealed that BSBT5 glass containing higher Bi2 O3 mol% exhibits maximum values of density, MAC, LAC, Z eff, N eff and minimum MFP, HVL and TVL. This indicates enhancement in the glass shielding properties with the addition of bismuth and the superiority of BSBT5 glass for radiation shielding applications compared to other studied glasses. Graphical Abstract: ga1